(untitled) (Eureka Journal of Physical and Chemical Research, 2025)
In the article Acorus calamus L. people treatment and scientific in medicine application according to information analysis Acorus calamus L medicinal fire there are many diseases, including neurological, gastrointestinal, respiratory intake, metabolic, kidney and liver diseases treatment for is used. In this review Acorus calamus L of in medicine various diseases in treatment participation about concept will be given.